1976
DOI: 10.1139/z76-221
|View full text |Cite
|
Sign up to set email alerts
|

Developmental rates of embryos of Atlantic salmon, Salmo salar L., in response to various levels of temperature, dissolved oxygen, and water exchange

Abstract: Embryos of Atlantic salmon. Salmo salur L., were incubated from fertilization to completion of hatching at 5 and 10 °C, at 20, 50, and 100% air-saturation, and at several rates of water exchange from 0.2 to 15 ml/s. Developmental rate to various structural stages, expressed as the reciprocal of time units, and hatching time were significantly controlled by temperature, oxygen supply, and rate of water exchange. Survival during embryogenesis and during the hatching period were limited primarily by oxygen supply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 11 publications
4
52
0
2
Order By: Relevance
“…Dissolved O 2 was monitored daily in the normoxic (98.7±0.4%) and hypoxic (29.7±0.5%) treatment tanks throughout the experiment (Hach LDO101 electrode connected to Hach HQ30d meter, Hach Company, Mississauga, ON, Canada). Because hypoxia exposure delays salmonid development (Shumway et al, 1964;Hamor and Garside, 1976;Ciuhandu et al, 2005;Miller et al, 2008), embryo sampling was stage-matched for the two treatment groups. Embryos were sampled at Vernier Stages 27 (prehatch; circulatory system is formed and functioning), 30 (hatch), 32 and 33 (in preliminary experiments a large increase in P 50 was observed between these stages), and 35 (near-complete yolk absorption; Fig.…”
Section: Experimental Protocol Treatment Conditionsmentioning
confidence: 99%
“…Dissolved O 2 was monitored daily in the normoxic (98.7±0.4%) and hypoxic (29.7±0.5%) treatment tanks throughout the experiment (Hach LDO101 electrode connected to Hach HQ30d meter, Hach Company, Mississauga, ON, Canada). Because hypoxia exposure delays salmonid development (Shumway et al, 1964;Hamor and Garside, 1976;Ciuhandu et al, 2005;Miller et al, 2008), embryo sampling was stage-matched for the two treatment groups. Embryos were sampled at Vernier Stages 27 (prehatch; circulatory system is formed and functioning), 30 (hatch), 32 and 33 (in preliminary experiments a large increase in P 50 was observed between these stages), and 35 (near-complete yolk absorption; Fig.…”
Section: Experimental Protocol Treatment Conditionsmentioning
confidence: 99%
“…DO levels in the water were monitored using a Luminescent Dissolved Oxygen (LDO TM ) meter (model HQ40d-LDO101, Hach Co., Loveland, CO, USA). Hypoxic exposure results in developmental delay (Hamor and Garside, 1976) and therefore measurements for this group were stage-matched with the normoxic group. Fig.1 is a picture of two larvae from the same fertilization event but reared under chronic hypoxia or control conditions.…”
Section: Series I: Adrenergic and Cholinergic Cardiac Responsementioning
confidence: 99%
“…In addition, the encapsulated, non-motile embryos may remain under these conditions for up to 5 months prior to emergence (Youngson et al, 2004). Previous work has demonstrated that embryonic development of teleost fish is extremely sensitive to environmental conditions (Ørnsrud et al, 2004) and that chronic hypoxia exposure delays development in fish (Shumway et al, 1964;Hamor and Garside, 1976;Ciuhandu et al, 2005;Spicer and Burggren, 2003;Bagatto, 2005;Miller et al, 2008). The reduction in developmental rate represents an adaptive response to reduce O 2 demand (Miller et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…De plus, mis à part MASON (1969) sur !e saumon coho (Oncorhyncus kisutch), les travaux déjà réalisés en conditions contrôlées ne décrivent pas les effets sublétaux possibles lors d'hypoxies temporaires (WICKETT, 1954 ;ALDERDICE et al, 1958 ;GARSIDE, 1966 ;HAMOR et GARSIDE, 1976et 1977.…”
Section: Introductionunclassified